Photothermal-modulated drug delivery and magnetic relaxation based on collagen/poly(γ-glutamic acid) hydrogel - Cho SH (Dove Medical Press, 2017)
Sun-Hee Cho,1,* Ahreum Kim,1,* Woojung Shin,2 Min Beom Heo,1 Hyun Jong Noh,1 Kwan Soo Hong,3,4 Jee-Hyun Cho,3,4 Yong Taik Lim1,2 1SKKU Advanced Institute of Nanotechnology (SAINT), 2School of Chemical Engineering, Sungkyunkwan University, Suwon, 3Bioimaging Research Team, Korea Basic Science Institute, Cheongju, 4Immunotherapy Convergence Research Center, Korea Research Institute of Bioscience and Biotechnology, Daejeon, Republic of Korea *These authors contributed equally to this work Abstract: Injectable and stimuli-responsive hydrogels have attracted attention in molecular imaging and drug delivery because encapsulated diagnostic or therapeutic components in the hydrogel can be used to image or change the microenvironment of the injection site by controlling various stimuli such as enzymes, temperature, pH, and photonic energy. In this study, we developed a novel injectable and photoresponsive composite hydrogel composed of anticancer drugs, imaging contrast agents, bio-derived collagen, and multifaceted anionic polypeptide, poly (γ-glutamic acid) (γ-PGA). By the introduction of γ-PGA, the intrinsic temperature-dependent phase transition behavior of collagen was modified to a low viscous sol state at room temperature and nonflowing gel state around body temperature. The modified temperature-dependent phase transition behavior of collagen/γ-PGA hydrogels was also evaluated after loading of near-infrared (NIR) fluorophore, indocyanine green (ICG), which could transform absorbed NIR photonic energy into thermal energy. By taking advantage of the abundant carboxylate groups in γ-PGA, cationic-charged doxorubicin (Dox) and hydrophobic MnFe2O4 magnetic nanoparticles were also incorporated successfully into the collagen/γ-PGA hydrogels. By illumination of NIR light on the collagen/γ-PGA/Dox/ICG/MnFe2O4 hydrogels, the release kinetics of Dox and magnetic relaxation of MnFe2O4 nanoparticles could be modulated. The experimental results suggest that the novel injectable and NIR-responsive collagen/γ-PGA hydrogels developed in this study can be used as a theranostic platform after loading of various molecular imaging probes and therapeutic components. Keywords: hydrogel, photothermal, near-infrared, drug delivery, magnetic nanoparticles